2014
DOI: 10.3109/15376516.2014.943444
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium induces mitophagy through ROS-mediated PINK1/Parkin pathway

Abstract: The results showed that Cd significantly induced MMP collapse and typical mitophagosomes formation, increased LC3-II/LC3-I ratio and PINK1 level, and decreased mitochondrial mass, revealing that Cd could induce mitophagy. However, NAC or ALC pretreatment markedly decreased Cd-induced ROS and simultaneously rescued MMP and mitochondrial mass, suggesting ROS played a crucial role in regulating mitophagy. NAC or ALC also dramatically lessened PINK1 level and mitochondrial accumulation of Parkin, indicating that R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Recent studies have suggested that Cd can induce mitophagy in mouse kidney and liver cells (Pi et al, 2013;Wei et al, 2014). Our data showed that Cd also could induce mitophagy in mouse brain.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Recent studies have suggested that Cd can induce mitophagy in mouse kidney and liver cells (Pi et al, 2013;Wei et al, 2014). Our data showed that Cd also could induce mitophagy in mouse brain.…”
Section: Discussionmentioning
confidence: 47%
“…ROS can damage mitochondria and are typically associated with mitophagy in yeast and mouse kidney (Kurihara et al, 2012;Wei et al, 2014). The present study also suggested that Cd induced excess ROS production and addressed the role of ROS in Cdinduced mitophagy in mouse brain.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Other studies have demonstrated that ROS plays a crucial role in regulating mitophagy. Cadmium induced ROS-mediated mitophagy through PINK1/Parkin pathway in kidneys of mice [35, 36]. However, the effects of IOCM and LOCM on mitochondrial ROS generation and mitochondrial damage still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Defective removal of damaged mitochondria could lead to increased ROS amounts with consequent accumulation of mutations in mitochondrial and nuclear DNA, thus favouring cancer onset. Mitophagy has been implicated in the removal of damaged mitochondria containing high levels of ROS [136,137] and ROS accumulation can promote by itself mitophagy activation, for example through mitochondrial membrane depolarization and Parkin/PINK1 pathway activation [138,139], thereby inhibiting initial tumor growth. Indeed, Parkin deficient mice spontaneously develop hepatic tumors [140], and PINK1 mutations have been described in neuroblastoma [141].…”
Section: Mitochondrial Dynamics and Mitophagy In Cancermentioning
confidence: 99%